Field reports form for submitting seasonal observations of Iowa birds, James Hansen, fall 1983 - Hansen, James L.et al (1983)
An annotated list of birds sighted by James Hansen. This item was used as supporting documentation for the Iowa Ornithologists Union Quarterly field report of fall 1983. Epson - sheet feed